Synthesis of N-[{5-Aryl-1, 3, 4-oxadiazole-2-yl}methyl]-4-methoxyaniline Derivatives and Their Anticonvulsant Activity. (23rd July 2013) - Prasanna Kumar, B. N.; Mohana, K. N.; Mallesha, L.
Abstract : A series of some new 2, 5-disubstituted-1, 3, 4-oxadiazoles 4(a–i) have been conveniently synthesized by intramolecular oxidative cyclization of (E)-2-(arylbenzylidene)-2-[(4-methoxyphenyl)amino]acetohydrazides promoted by iodobenzene diacetate as an oxidant. The structures of the synthesized compounds have been confirmed by 1 H and 13 C NMR, IR, MS, and elemental analysis. All the newly synthesized compounds were screened for their anticonvulsant activity against maximal electroshock (MES) seizure method. Compounds 4g, 4d, and 4a were found to be the most potent of this series. The same compounds showed no neurotoxicity at the maximum dose administered.